2007
DOI: 10.1111/j.1365-2524.2007.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoke-free spaces over time: a policy diffusion study of bylaw development in Alberta and Ontario, Canada

Abstract: Policy diffusion is a process whereby political bodies 'learn' policy solutions to public health problems by imitating policy from similar jurisdictions. This suggests that diffusion is a critical element in the policy development process, and that its role must be recognised in any examination of policy development. Yet, to date, no systematic work on the diffusion of smoke-free spaces bylaws has been reported. We examined the diffusion of municipal smoke-free bylaws over a 30-year period in the provinces of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…Thus, regulatory activity at the higher level of jurisdiction (province) may play a part in policymaking in lower jurisdictions (municipalities); e.g., decision-makers may become stalled by debates of jurisdictional propriety over SHS regulation. In a policy diffusion study [21], rates of municipal smoke-free bylaw adoption dropped substantially in years where there was tobacco control policy activity at the provincial level, regardless of whether or not the provincial activity was directly related to smoke-free spaces. Thus the importance of provincial tobacco control context for local smoke-free bylaw development is another critical point for those in public health working with these issues.…”
Section: Contextualmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, regulatory activity at the higher level of jurisdiction (province) may play a part in policymaking in lower jurisdictions (municipalities); e.g., decision-makers may become stalled by debates of jurisdictional propriety over SHS regulation. In a policy diffusion study [21], rates of municipal smoke-free bylaw adoption dropped substantially in years where there was tobacco control policy activity at the provincial level, regardless of whether or not the provincial activity was directly related to smoke-free spaces. Thus the importance of provincial tobacco control context for local smoke-free bylaw development is another critical point for those in public health working with these issues.…”
Section: Contextualmentioning
confidence: 99%
“…Further, a diffusion of innovation perspective suggests that decision-makers often utilize policies that have been successfully implemented in other jurisdictions [17,19,20]. This possibility was investigated in a separate study conducted by Nykiforuk et al [21] exploring patterns of bylaw diffusion across municipalities and health regions. This study found that geographic diffusion and adopter (community) characteristics worked in concert with local, provincial and national tobacco control activities to explain bylaw adoption patterns across provinces.…”
Section: Introductionmentioning
confidence: 99%
“…Government decision-makers could be reassured (based on KAB findings) that, in fact, most policy influencers in the province along with the general public supported such a policy, then they may act on the issue without fear of upsetting constituents. A deeper understanding of public support patterns can then be used by advocates to support strategic policy diffusion across a region or state [80][81][82].…”
Section: Implications For Policy Advocacy and Implementationmentioning
confidence: 99%
“…143 Mandatory vaccination programs, smoking bylaws, and seat belt legislation are examples of initiatives where individual freedoms have been limited in the interest of the public good. [144][145][146] The chiropractic profession encourages its members' responsibility to public health promotion, 1,10 and this is recognized in several codes of ethics. [138][139][140] For example, the Canadian Chiropractic Association's Code of Ethics and conduct guides its members to "accept full share of the chiropractic profession's responsibility to society in matters relating to spinal and public health, health education, and legislation affecting the health or well-being of the citizens of the community."…”
Section: Stacey a Page Phdmentioning
confidence: 99%